2016
DOI: 10.2218/pihph.1.2016.1698
|View full text |Cite
|
Sign up to set email alerts
|

Sociolinguistic motivations in sound change: on-going loss of low tone breathy voice in Shanghai Chinese

Abstract: This study focuses on the ongoing disappearance of low tone breathiness in Shanghai Chinese. In the change from a voicing contrast to a tone register contrast in Sinitic languages, the ancient voiced series was characterised by a breathy voice quality, which remained as a secondary and redundant cue of low tones in Shanghai Chinese. This study, using transversal production data from 12 young and 10 elderly speakers, shows that low tone breathiness is better preserved by elderly than young speakers, and by male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Our understanding of phonation contrasts, along with the tools for extensive voice analysis, have greatly advanced during the last decade. Recently, the phonetic properties of the Shanghainese register contrast have been revisited in several studies (Gao, 2016;Tian & Kuang, 2016;Gao & Hallé, 2017;Zhang & Yan, 2018) with mostly younger speakers (born after 1980).…”
Section: Registermentioning
confidence: 99%
See 1 more Smart Citation
“…Our understanding of phonation contrasts, along with the tools for extensive voice analysis, have greatly advanced during the last decade. Recently, the phonetic properties of the Shanghainese register contrast have been revisited in several studies (Gao, 2016;Tian & Kuang, 2016;Gao & Hallé, 2017;Zhang & Yan, 2018) with mostly younger speakers (born after 1980).…”
Section: Registermentioning
confidence: 99%
“…In any event, older speakers' production should be examined in order to understand the phonetic properties of the Shanghainese phonation contrast. (2012) Less tension in the entire vocal tract; less amount of change in tension than breathy voice Follow Laver (1980) Follow Laver (1980 Moreover, although existing studies of older speakers' production (including more recently Tian &Gao &Hallé, 2017) suggest that the non-modal phonation in Shanghainese is generally breathier (i.e., produced with relatively less glottal constriction), it remains unclear whether this breathier voice in Shanghainese is similar to or different from the breathier voices in other languages. As noted by Catford (1977), Laver (1980) and Ladefoged & Maddieson (1996), there is substantial cross-linguistic variation for so-called 'breathier voice.…”
Section: Registermentioning
confidence: 99%
“…Some sound changes involve a non-primary cue taking over the role of a primary cue as occurs in 'tonogenesis' (Kingston, 2011), for example, the case of some younger speakers of Afrikaans shifting from VOT to f0 to signal a voicing contrast (Coetzee, Beddor, Shedden, Styler, & Wissing, 2018). In contrast, in the case of Shanghai Wu, a non-primary cue (i.e., breathiness) to the register contrast is losing importance (Gao, 2016). We thus may expect to observe increased individual variability in the use of non-primary cues in a variety undergoing sound change (though see Coetzee et al, 2018 perception data).…”
Section: Multiple Cues: Individual Variability and Sound Changementioning
confidence: 99%
“…While both Shanghai and Jiashan dialects share the same characteristics of register contrast, the Shanghai dialect is argued to be going through a loss of breathiness in the lower register, at least in production (Gao, 2016;Gao et al, 2011). Based on their acoustic and electroglottographic data, Gao and colleagues found that younger speakers used less breathy voice in the lower register compared to older speakers, possibly due to contact with Mandarin Chinese which does not employ breathy voice in tonal contrasts.…”
Section: Wu Chinesementioning
confidence: 99%
See 1 more Smart Citation